2019
DOI: 10.1182/bloodadvances.2018025155
|View full text |Cite
|
Sign up to set email alerts
|

Platelet respiration

Abstract: Historically, metabolic studies in platelets have primarily investigated events occurring during ex vivo platelet storage, less so the consequences of metabolic alterations on platelet homeostasis and physiologic function. The importance of such studies is emphasized by the recent finding of platelet mitochondrial dysfunction in type 2 diabetes, sickle cell disease, and sepsis. [1][2][3][4][5][6][7] These early investigations used radiometric methods with labeled glucose to study glycolysis and oxidative phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 26 publications
(35 reference statements)
1
14
0
Order By: Relevance
“…PLTs are highly dependent on mitochondrial activity and aerobic respiration 30 . Acetate is the major source of energy in PAS‐containing PLTs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PLTs are highly dependent on mitochondrial activity and aerobic respiration 30 . Acetate is the major source of energy in PAS‐containing PLTs.…”
Section: Resultsmentioning
confidence: 99%
“…A key parameter defining mitochondrial activity is the oxygen consumption rate (OCR). Aerobic respiration is characterized by increased OCR, while alternative anaerobic respiration is independent of oxygen consumption 30 . Intuitively, refrigeration should result in a decrease in the metabolic needs of stored PLTs.…”
Section: Resultsmentioning
confidence: 99%
“…MtDNA copy number is considered to reflect mitochondrial function 24 . Healthy platelets contain between 5 and 8 mitochondria, which serve important processes such as platelet activation, ATP production and platelet viability 25 29 . Platelets are traditionally known for their role in hemostasis, but an increasing body of evidence supports their role in key processes beyond hemostasis, including inflammation and immunoregulation 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Platelet activation with thrombin has been reported to cause significant changes to platelet metabolism, particularly in regard to glucose uptake, extracellular acidification, and oxygen consumption (Aibibula et al, 2018, Nayak et al, 2018, Ravi et al, 2015). Agonist induced platelet activation initiates a step change in energy requirements, and as a result, activated platelets exhibit increased oxidative phosphorylation and glycolysis to accommodate increased ATP demands (Kholmukhamedov and Jobe, 2019). Previous studies have observed that activated platelets show increased glycolysis relative to mitochondrial phosphorylation (Kramer, 2014).…”
Section: Discussionmentioning
confidence: 99%